Nanosheet Pd-based catalyst and its application in catalytic hydrogenation of NBR

The preparation of oxygen-deficient nitrogen-doped titanium dioxide nanosheet carriers and the equal volume impregnation method is carried out to form a nanosheet-shaped catalyst, which solves the problems of catalyst separation difficulty and loss of active metals, and realizes the preparation of high-efficiency hydrogenated nitrile rubber. Suitable for industrial production.

CN116273125BActive Publication Date: 2025-01-17FUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310292206.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-01-17
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

In the existing NBR hydrogenation process, it is difficult to separate the catalyst from the product, resulting in high production costs, and active metals are easily lost during heterogeneous hydrogenation, affecting the reusability and hydrogenation efficiency of the catalyst.

Method used

Titanium dioxide nanosheets were prepared by hydrothermal method as support, oxygen vacancy defects and nitrogen doping were introduced through NH3/N2 high-temperature pretreatment, and combined with equal volume impregnation method to support the active metal Pd to form a nanosheet-shaped Pd/TiO2 catalyst for nitrile Catalytic hydrogenation of rubber.

Benefits of technology

It improves the utilization rate of active sites and the reusability of catalysts, achieves efficient hydrogenation effect, reduces metal residues and production costs, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273125B_ABST
    Figure CN116273125B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation of a nano-sheet Pd-based catalyst and its application in catalytic hydrogenation of nitrile rubber, wherein a titanium dioxide nanosheet prepared by a hydrothermal method is used as a carrier, an oxygen vacancy defect is constructed thereon by a NH3 / N2 high temperature pretreatment method and N species are introduced, and then the active metal Pd is loaded by an equal volume impregnation method, and then the nano-sheet Pd-based catalyst is obtained by reduction. The oxygen vacancy defects and N species on the surface of the titanium dioxide nanosheet carrier in the catalyst can be used together as active component anchoring points to achieve efficient and stable loading of Pd, which enhances the metal-carrier interaction, is conducive to improving the stability of the catalyst, and is applied to the hydrogenation reaction of NBR, with efficient catalytic performance and good recycling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic hydrogenation of high molecular weight unsaturated polymers, and specifically relates to the preparation of a nano-sheet Pd-based catalyst and the application of the catalyst in the catalytic hydrogenation of nitrile rubber. Background Art

[0002] Nitrile rubber (NBR) is a polar rubber made by low-temperature emulsion polymerization of acrylonitrile and butadiene monomers. The presence of nitrile groups in its molecules makes it stable to non-polar and weakly polar oils and low aromatic solvents, so it is widely used in oil-resistant products. However, due to the presence of unsaturated C=C double bonds in the molecular chain of nitrile rubber, its oxidation resistance, aging resistance and ozone resistance are poor, resulting in its comprehensive performance failing to meet the requirements of high-end applications. On the premise of retaining the nitrile group, the unsaturated C=C double bonds in the NBR molecular chain are hydrogenated to saturate, and high-performance, high-value-added hydrogenated nitrile rubber (HNBR) can be obtained. HNBR has the advantages of NBR and also has excellent corrosion resistance, ozone resistance, extrusion deformation resistance, wear resistance, tear resistance and other characteristics. Its comprehensive performance is extremely excellent and it is widely used in the automotive, aerospace, petrochemical and other industries.

[0003] At present, the main NBR hydrogenation processes include solution hydrogenation, emulsion hydrogenation and ethylene-acrylonitrile copolymerization. Among them, the solution hydrogenation method has been industrialized, and according to the different catalysts used, it is divided into homogeneous solution hydrogenation and heterogeneous solution hydrogenation. The homogeneous solution hydrogenation process has mild reaction conditions and excellent hydrogenation performance, but it is difficult to separate the catalyst from the hydrogenation product after the reaction, which increases the production cost. At the same time, the precious metals remaining in the rubber will seriously reduce the physical and chemical properties of the rubber. Inhomogeneous solution hydrogenation can separate the product from the catalyst by simple centrifugation, avoiding the catalyst from remaining in the product, greatly reducing the cost of NBR hydrogenation, and has a good prospect for industrial application.

[0004] Patent CN 104119478A mentions that Pd / TiO2 catalyst can be used for NBR heterogeneous hydrogenation, but the results show that only when the Pd loading is as high as 5 wt.%, the HNBR hydrogenation degree can reach more than 90%. The catalyst prepared by this method has low utilization rate of Pd active sites and high production cost, which is not conducive to industrial production. This is mainly due to the high viscosity of NBR glue and obvious steric hindrance effect. Therefore, in the heterogeneous hydrogenation process, the diffusion restriction of macromolecular polymers in the catalyst pores and the efficient loading of active sites have become the key to affecting the hydrogenation efficiency.

[0005] Combined with the currently reported literature and patents, designing catalysts with macroporous structures or two-dimensional layered structures can effectively eliminate the pore diffusion limitations of polymers. However, active metals are easily lost from the surface of the carrier during high-speed stirring reactions, thereby reducing the reusability of the catalyst. In order to avoid the problem of precious metal loss caused by weak interaction between the active component and the carrier, the carrier surface is usually functionally modified to achieve efficient and stable loading of the active component (such as patent CN107308985A), but the modification process consumes a large amount of organic solvents, causing environmental pollution while increasing production costs. Therefore, the development of a green, low-cost, highly dispersed, and highly stable supported Pd-based catalyst is of great significance and use value for the industrial production of high-value-added HNBR. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a nano-sheet Pd-based catalyst and a method for preparing hydrogenated nitrile rubber by catalytic hydrogenation thereof.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A nano-sheet Pd-based catalyst, which uses a titanium dioxide nanosheet prepared by a hydrothermal method as a carrier, constructs oxygen vacancy defects and introduces N species on the titanium dioxide nanosheet by a NH3 / N2 high-temperature pretreatment method, and then loads active metal Pd by an equal volume impregnation method, and then reduces the catalyst to obtain the catalyst; the preparation method specifically comprises the following steps:

[0009] 1) Preparation of titanium dioxide nanosheets: Tetrabutyl titanate was dispersed in anhydrous ethanol to prepare a tetrabutyl titanate dispersion with a concentration of 40 wt.%, and after stirring for 10 min, hydrofluoric acid was added dropwise, and the mixture was stirred for 15 min. The mixture was transferred into a hydrothermal reactor and crystallized at 180 °C for 8-12 h. After the reaction was completed, the mixture was cooled to room temperature and washed with deionized water until neutral. The product was then dispersed in a 0.1-1 M sodium hydroxide solution and stirred. The product was washed with deionized water and ethanol several times until neutral. The obtained sample was placed in a muffle furnace, heated to 450 °C at a rate of 5 °C / min, and calcined for 2-4 h to obtain titanium dioxide nanosheets.

[0010] 2) NH3 / N2 high temperature pretreatment: The prepared titanium dioxide nanosheets are placed in a tube furnace, and a mixed gas of NH3 / N2 (5:95, v / v) is introduced, and the temperature is raised to 450-600 °C at a rate of 5 °C / min, and the treatment is carried out for 4-10 h, thereby obtaining titanium dioxide nanosheets with oxygen vacancy defects and nitrogen doping on the surface;

[0011] 3) Loading metal Pd by equal volume impregnation method: Add the metal palladium precursor into the solvent to prepare a solution, then add it dropwise into the titanium dioxide nanosheets with oxygen vacancy defects and nitrogen doping on the surface until the initial wet state is reached, and then let it stand for 6-12 hours;

[0012] 4) Reduction: In a H2 / Ar (10:90, v / v) mixed atmosphere, the temperature was raised to 140 °C at a rate of 2 °C / min and maintained for 2 h to obtain a nanosheet Pd / TiO2 catalyst.

[0013] Furthermore, the molar ratio of tetrabutyl titanate to hydrofluoric acid used in step 1) is 13:100.

[0014] Furthermore, in step 3), the precursor of the metal palladium is one or more of palladium acetate, palladium chloride, palladium nitrate, and palladium acetylacetonate, preferably palladium acetate and / or palladium chloride; the solvent is one or more of dichloromethane, hydrochloric acid, deionized water, and ethylene glycol, preferably dichloromethane and / or hydrochloric acid.

[0015] Furthermore, the loading amount of active metal Pd in ​​the obtained catalyst is 0.1-1 wt.%, preferably, the loading amount of active metal Pd is 0.5-1 wt.%.

[0016] The nano-sheet Pd-based catalyst prepared above can be used in the reaction of preparing hydrogenated nitrile rubber by catalytic hydrogenation of nitrile rubber. The specific application method is to dissolve the nitrile rubber in an organic solvent to obtain a solution with a concentration of 1-10 wt.%, add the nano-sheet Pd-based catalyst therein, and then react for 2-8 hours at 30-120 ° C and a hydrogen pressure of 0.5-6 MPa (preferably 60-120 ° C and 1-6 MPa). After the reaction is completed, the obtained reaction liquid is centrifuged, and the obtained upper layer liquid is flocculated with deionized water to obtain hydrogenated nitrile rubber; the lower layer catalyst is recovered and used.

[0017] Furthermore, the organic solvent is one or more of acetone, cyclohexane, chlorobenzene, cyclohexanone, butanone, decahydronaphthalene, and tetrahydrofuran, preferably acetone and / or chlorobenzene.

[0018] Furthermore, the mass ratio of the nanosheet Pd-based catalyst to the nitrile rubber is 0.1-1:1.

[0019] The titanium dioxide nanosheets prepared by the hydrothermal method of the present invention are of a two-dimensional layered structure, which can not only provide a high external specific surface area that is conducive to the efficient dispersion of active components, but also eliminate the diffusion restriction of NBR polymer molecules in the catalyst pores, effectively improve the accessibility of active components and NBR molecules, increase the utilization rate of active sites, and enable it to achieve higher catalytic activity at a lower loading amount; oxygen vacancy defects and N species can be used together as anchoring points of active components, which is conducive to efficient and stable anchoring and dispersion of active components, so as to achieve the purpose of simple recovery and reuse of catalysts; nitrogen-doped defective TiO2 nanosheets can solve the problems of easy loss of active metals, low utilization rate of active sites, slow mass transfer rate, etc. caused by high viscosity and complex configuration of polymer colloid in heterogeneous hydrogenation of NBR.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention uses titanium dioxide nanosheets containing oxygen defects and nitrogen doping as carriers. The nanosheet structure can provide a high external specific surface area to facilitate the efficient dispersion of active components. The oxygen vacancy defects and N species can jointly serve as anchoring points for active metals to efficiently and stably load Pd. There is obvious electron transfer between N and Pd, which makes the metal-carrier have a strong interaction, thereby facilitating the improvement of the hydrogenation activity and reusability of the catalyst.

[0022] (2) The Pd / TiO2 nanosheet catalyst prepared in the present invention has a two-dimensional layered structure, which can effectively avoid the diffusion restriction of macromolecular polymers in the catalyst pores, facilitate the full contact between NBR and active metals, improve the utilization rate of active sites, and further improve the hydrogenation activity of the catalyst.

[0023] (3) The catalyst preparation process of the present invention is simple and easy. The Pd nanoparticles are small in size (1.1 nm), highly dispersed, have excellent hydrogenation effect (HD>96%), low metal residue (1.3 ppm), and good recyclability (HD>93%), which has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The EPR graph (a) and XPS graph (b) of the titanium dioxide nanosheet obtained after high temperature pretreatment in Example 1. The contents in the graphs can prove that there are oxygen vacancy defects and nitrogen doping in the obtained titanium dioxide nanosheet.

[0025] Figure 2 TEM image of the Pd / TiO2 nanosheet catalyst prepared in Example 1 and the Pd particle size distribution thereon.

[0026] Figure 3The SEM comparison pictures of titanium dioxide nanosheets (a) obtained after high temperature pretreatment in Example 1 and commercial titanium dioxide (b) are shown.

[0027] Figure 4 Figure 2 shows the N2 adsorption-desorption diagram (a) and pore size distribution diagram (b) of the titanium dioxide nanosheets obtained after high-temperature pretreatment in Example 1 and commercial titanium dioxide.

[0028] Figure 5 The infrared spectra of HNBR prepared by hydrogenation reaction in Example 1 and Comparative Example 1 are compared. DETAILED DESCRIPTION

[0029] A method for preparing a nano-sheet Pd-based catalyst comprises the following steps:

[0030] 1) Preparation of titanium dioxide nanosheets: Tetrabutyl titanate was dispersed in anhydrous ethanol to prepare a tetrabutyl titanate dispersion with a concentration of 40 wt.%, and after stirring for 10 min, hydrofluoric acid was added dropwise at a molar ratio of 100:13 to tetrabutyl titanate. After stirring for 15 min, it was transferred into a hydrothermal reactor and crystallized at 180 °C for 8-12 h. After the reaction was completed, it was cooled to room temperature and washed with deionized water until neutral. The product was then dispersed in a 0.1-1 M sodium hydroxide solution and continued to be stirred. After washing with deionized water and ethanol several times until neutral, the obtained sample was placed in a muffle furnace, heated to 450 °C at a rate of 5 °C / min, and calcined for 2-4 h to obtain titanium dioxide nanosheets.

[0031] 2) NH3 / N2 high temperature pretreatment: The prepared titanium dioxide nanosheets are placed in a tube furnace, and a mixed gas of NH3 / N2 (5:95, v / v) is introduced, and the temperature is raised to 450-600 °C at a rate of 5 °C / min, and the treatment is carried out for 4-10 h, thereby obtaining titanium dioxide nanosheets with oxygen vacancy defects and nitrogen doping on the surface;

[0032] 3) Loading metal Pd by equal volume impregnation method: Add the metal palladium precursor into the solvent to prepare a solution, then add it dropwise into the titanium dioxide nanosheets with oxygen vacancy defects and nitrogen doping on the surface until the initial wet state is reached, and then let it stand for 6-12 hours;

[0033] 4) Reduction: In a H2 / Ar (10:90, v / v) mixed atmosphere, the temperature was raised to 140 °C at a rate of 2 °C / min and maintained for 2 h to obtain a catalyst Pd / TiO2 with a loading of active metal Pd of 0.1-1 wt.%;

[0034] The precursor of the metal palladium is one or more of palladium acetate, palladium chloride, palladium nitrate, and palladium acetylacetonate; and the solvent is one or more of dichloromethane, hydrochloric acid, deionized water, and ethylene glycol.

[0035] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0036] In the embodiments and comparative examples, the SEM images were obtained by a Japanese S-4800 scanning electron microscope; the EPR images were obtained by a German ELEXSYS-II E500 electron paramagnetic resonance spectrometer; the XPS images were obtained by an American ESCA Lab 250 X-ray photoelectron spectrometer; the N2 adsorption-desorption images were obtained by an American ASAP 2460 physical adsorption instrument; the TEM images were obtained by an American TecnaiG2F20 transmission electron microscope; and the infrared spectra were obtained by an American Nicolet iS50 FTIR spectrometer.

[0037] Example 1

[0038] 10 g of tetrabutyl titanate was dispersed in 15 g of anhydrous ethanol, stirred for 10 min, 4.5 g of hydrofluoric acid was weighed and added dropwise, stirred for 15 min, and then transferred into a hydrothermal reactor, crystallized at 180 °C for 9 h, cooled to room temperature after the reaction was completed, washed with deionized water until neutral, and then dispersed in 0.1 M sodium hydroxide solution, and continued to stir for 6 h, and finally washed with deionized water and ethanol several times until neutral, and then heated to 450 °C at a rate of 5 °C / min in a muffle furnace, and calcined for 2 h to obtain titanium dioxide nanosheets;

[0039] The titanium dioxide nanosheets prepared above were placed in a tubular furnace with a NH3 / N2 (5:95, v / v) mixed gas, and the temperature was increased to 550°C at a rate of 5°C / min and maintained for 6 h to obtain titanium dioxide nanosheets with oxygen vacancy defects and N doping on the surface; 1.0 g of the obtained titanium dioxide nanosheets were spread flat in a beaker, and 2.0 ml of a dichloromethane solution containing 0.0213 g of palladium acetate was added dropwise, and stirred evenly until the initial wet state was obtained. After standing at room temperature for 12 h, the mixture was transferred to an oven for drying for 12 h, and then heated to 140°C at a rate of 2°C / min in a tubular furnace with a H2 / Ar (10:90, v / v) mixed gas, and maintained for 2 h to obtain a Pd / TiO2 nanosheet catalyst with a Pd loading of 1 wt.%.

[0040] 1.0 g of NBR was dissolved in 80 g of acetone, and then 1.0 g of the Pd / TiO2 nanosheet catalyst prepared above was added to carry out catalytic hydrogenation reaction in a high-pressure reactor. The reaction conditions were: temperature 60 °C, hydrogen pressure 2 MPa, stirring rate 800 rpm, and reaction time 3 h. After the reaction, the obtained reaction solution was centrifuged, the obtained catalyst was recovered and used, and deionized water was added to the obtained glue to flocculate to obtain the product HNBR. The product hydrogenation degree is listed in Table 1.

[0041] Example 2

[0042] The calcination temperature of the titanium dioxide nanosheets obtained in Example 1 in the NH3 / N2 (5:95, v / v) mixed gas was changed to 450°C. Other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 1.

[0043] Example 3

[0044] The calcination temperature of the titanium dioxide nanosheets obtained in Example 1 in the NH3 / N2 (5:95, v / v) mixed gas was changed to 500°C. Other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 1.

[0045] Example 4

[0046] The calcination temperature of the titanium dioxide nanosheets obtained in Example 1 in the NH3 / N2 (5:95, v / v) mixed gas was changed to 600°C. Other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 1.

[0047] Table 1 Effect of different calcination temperatures on NBR hydrogenation degree

[0048]

[0049] Example 5

[0050] The calcination time of the titanium dioxide nanosheets obtained in Example 1 in the NH3 / N2 (5:95, v / v) mixed gas was changed to 4 h. Other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 2.

[0051] Example 6

[0052] The calcination time of the titanium dioxide nanosheets obtained in Example 1 in the NH3 / N2 (5:95, v / v) mixed gas was changed to 8 h. Other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 2.

[0053] Example 7

[0054] The calcination time of the titanium dioxide nanosheets obtained in Example 1 in the NH3 / N2 (5:95, v / v) mixed gas was changed to 10 h. Other operations were the same as in Example 1. The hydrogenation degree of the product is shown in Table 2.

[0055] Table 2 Effect of different calcination times on NBR hydrogenation degree

[0056]

[0057] Example 8

[0058] The temperature of the hydrogenation reaction in Example 1 was controlled at 80°C, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 3.

[0059] Example 9

[0060] The temperature of the hydrogenation reaction in Example 1 was controlled at 100°C, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 3.

[0061] Example 10

[0062] The temperature of the hydrogenation reaction in Example 1 was controlled at 120°C, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 3.

[0063] Table 3 Effect of different hydrogenation reaction temperatures on NBR hydrogenation degree

[0064]

[0065] Embodiment 11

[0066] The pressure of the hydrogenation reaction in Example 1 was controlled at 1 MPa, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 4.

[0067] Example 12

[0068] The pressure of the hydrogenation reaction in Example 1 was controlled at 3 MPa, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 4.

[0069] Example 13

[0070] The pressure of the hydrogenation reaction in Example 1 was controlled at 6 MPa, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 4.

[0071] Table 4 Effect of different hydrogenation reaction pressures on NBR hydrogenation degree

[0072]

[0073] Embodiment 14

[0074] The time of hydrogenation reaction in Example 1 was controlled at 2 h, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 5.

[0075] Embodiment 15

[0076] The time of the hydrogenation reaction in Example 1 was controlled at 4 h, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 5.

[0077] Example 16

[0078] The time of the hydrogenation reaction in Example 1 was controlled at 8 h, and other operations were the same as in Example 1. The degree of hydrogenation of the product is shown in Table 5.

[0079] Table 5 Effect of different hydrogenation reaction times on NBR hydrogenation degree

[0080]

[0081] Embodiment 17

[0082] The Pd loading in Example 1 was adjusted to 0.5 wt.%, and other operations were the same as in Example 1. The product hydrogenation degree is shown in Table 6.

[0083] Embodiment 18

[0084] The Pd loading in Example 1 was adjusted to 0.6 wt.%, and other operations were the same as in Example 1. The product hydrogenation degree is shown in Table 6.

[0085] Embodiment 19

[0086] The Pd loading in Example 1 was adjusted to 0.8 wt.%, and other operations were the same as in Example 1. The product hydrogenation degree is shown in Table 6.

[0087] Table 6 Effect of different Pd loadings on NBR hydrogenation degree

[0088]

[0089] Embodiment 20

[0090] The catalyst recovered in Example 1 was used to repeat the catalytic hydrogenation of NBR according to the operation thereof. The degree of hydrogenation of the product is shown in Table 7.

[0091] Embodiment 21

[0092] The catalyst recovered in Example 20 was used to repeat the catalytic hydrogenation of NBR according to its operation. The degree of hydrogenation of the product is shown in Table 7.

[0093] Embodiment 22

[0094] The catalyst recovered in Example 21 was used to repeat the catalytic hydrogenation of NBR according to the operation thereof. The degree of hydrogenation of the product is shown in Table 7.

[0095] Table 7 Effect of different recycling times of catalyst on NBR hydrogenation degree

[0096]

[0097] Comparative Example 1

[0098] In order to verify the effect of NH3 / N2 pretreatment, this comparative example uses titanium dioxide nanosheets without high temperature pretreatment directly as a carrier, and uses the same method as Example 1 to load and reduce the active components, so as to compare with Example 1. The hydrogenation method and reaction conditions in Example 1 were used to investigate its catalytic hydrogenation performance on NBR, and the product hydrogenation degree is listed in Table 9.

[0099] Comparative Example 2

[0100] In order to verify the effect of the nanosheet structure, this comparative example uses commercial titanium dioxide as a carrier, and adopts the same method as Example 1 to carry out high-temperature pretreatment of the carrier and loading and reduction of the active components, so as to compare with Example 1. The hydrogenation method and reaction conditions in Example 1 were adopted to investigate its catalytic hydrogenation performance on NBR, and the hydrogenation degree of the product is listed in Table 9.

[0101] Comparative Example 3

[0102] In order to verify the effect of carrier defects and carrier morphology in the NBR hydrogenation reaction, this comparative example uses commercial titanium dioxide without high temperature pretreatment as a carrier, and uses the same method as Example 1 to load and reduce the active components, so as to compare with Example 1. The hydrogenation method and reaction conditions in Example 1 were used to investigate its catalytic hydrogenation performance on NBR, and the product hydrogenation degree is listed in Table 9.

[0103] Table 8 Comparison of specific surface area, pore volume and pore size of different carriers

[0104]

[0105] Table 8 is a performance comparison table of the titanium dioxide nanosheets obtained after high temperature pretreatment in Example 1 and the commercial titanium dioxide used. Figure 4 The N2 adsorption-desorption diagram and pore size distribution diagram of the titanium dioxide nanosheets obtained after high temperature pretreatment and commercial titanium dioxide in Example 1. It can be seen from the content of the diagram that the specific surface area, pore volume and pore size of commercial titanium dioxide are significantly smaller than those of the titanium dioxide nanosheets obtained after high temperature pretreatment in Example 1, and the large specific surface area and rich pore structure are the key to preparing highly dispersed and highly stable supported Pd-based catalysts.

[0106] Table 9 Effect of different catalysts on NBR hydrogenation degree and selectivity

[0107]

[0108] Figure 5This is a comparison of the infrared spectra of the NBR hydrogenation products obtained in Example 1 and Comparative Example 1. As can be seen from the figure, the NBR raw material has a wavelength of 970 and 920 cm -1 The characteristic absorption peaks of 1,4-trans-CH=CH- structure and 1,2-CH=CH2 at 723 cm-1 are more obvious. In the comparative examples and examples, the characteristic peaks of the double bond structure of the butadiene segment are significantly weakened with the increase of hydrogenation degree, and a new peak at 723 cm-1 appears. -1 (-CH2-) n , n>4 structure peak intensity gradually increased, proving that the comparative example and the example products are HNBR. As can be seen from Table 9, the degree of hydrogenation of Example 1 is better than that of each comparative example, which fully proves that NH3 / N2 atmosphere and nanosheet structure have an important influence on the preparation of high-performance supported Pd-based catalysts.

[0109] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a nano-sheet Pd-based catalyst for preparing hydrogenated nitrile rubber by catalytic hydrogenation of nitrile rubber, characterized in that: Titanium dioxide nanosheets prepared by a hydrothermal method are used as carriers, oxygen vacancy defects are constructed thereon and N species are introduced by high-temperature pretreatment with NH3 / N2, active metal Pd is loaded by an equal volume impregnation method, and then reduced to obtain the nanosheet Pd-based catalyst; The NH3 / N2 high temperature pretreatment is to place the titanium dioxide nanosheets in a tube furnace, introduce a mixed gas of NH3 / N2, heat the mixture to 450-600°C at a rate of 5°C / min, and treat for 4-10 hours, thereby obtaining titanium dioxide nanosheets with oxygen vacancy defects and nitrogen doping on the surface; the volume ratio of NH3 to N2 in the mixed gas is 5:95; The loading amount of active metal Pd in ​​the obtained catalyst is 0.1-1 wt.%.

2. The method for preparing the nanosheet Pd-based catalyst according to claim 1, characterized in that: The specific preparation method of the titanium dioxide nanosheet is as follows: tetrabutyl titanate is dispersed in anhydrous ethanol to prepare a tetrabutyl titanate dispersion with a concentration of 40 wt.%, and after stirring for 10 minutes, hydrofluoric acid is added dropwise, and stirring is continued for 15 minutes, and crystallization is carried out at 180°C for 8-12 hours. After the reaction is completed, it is cooled to room temperature, washed with deionized water until neutral, and then the product is dispersed in a 0.1-1 M sodium hydroxide solution and stirred continuously, and washed with deionized water and ethanol several times until neutral, and then placed in a muffle furnace, heated to 450°C at a rate of 5°C / min, and calcined for 2-4 hours to obtain the titanium dioxide nanosheet; The molar ratio of tetrabutyl titanate to hydrofluoric acid is 13:

100.

3. The method for preparing the nanosheet Pd-based catalyst according to claim 1, characterized in that: The equal volume impregnation method is to dissolve the precursor of metal palladium in a solvent to prepare a solution, and use the solution to impregnate the support; The precursor of the metal palladium is one or more of palladium acetate, palladium chloride, palladium nitrate, and palladium acetylacetonate; The solution is one or more of dichloromethane, hydrochloric acid, deionized water, and ethylene glycol; The immersion time is 6-12 h.

4. The method for preparing the nanosheet Pd-based catalyst according to claim 1, characterized in that: The reduction is carried out in a H2 / Ar mixed atmosphere, with the temperature raised to 140°C at a rate of 2°C / min and maintained for 2 h; The volume ratio of H2 to Ar in the mixed atmosphere is 10:90.

Citation Information

Patent Citations

  • Preparation and application method of selective heterogeneous solution hydrogenation catalyst of nitrile-butadiene rubber (NBR)

    CN107308985A

  • Novel method for synthesizing hydrogenated nitrile-butadiene rubber by using Pd / TiO2 catalyst

    CN104119478A

  • Defect site TiO2 loaded monatomic noble metal catalyst, preparation method and application thereof

    CN114602462A